A descriptive study on sex-related language in the subtitling of Succession into Spanish - José Javier Ávila-Cabrera; Pilar Rodríguez-Arancón (Cadernos de Tradução, 2025)
Sex can be considered a vulgar, forbidden or unwelcome topic in many contexts and this fact can add a challenge to subtitlers of audiovisual products depending on the cultures and languages involved (Ávila-Cabrera, 2024). Although some authors claim that sexual references tend to be altered, mitigated or omitted when dubbing (Ferrari, 2010; Scandura, 2021) and subtitling (Fuentes-Luque, 2020) from English into neutral Spanish, other researchers such as Villanueva-Jordán (2023) have demonstrated through a case study that neutral Spanish for the Latin American audience does retain sexual references in dubbing. This paper examines the subtitling of the four seasons of the TV series Succession (Armstrong, 2018–2023) from US English into Spanish (from Spain), as broadcast on Max (formerly HBO España). The primary objectives of the study are as follows: (1) to explore the extent to which sexual references from the source text are transferred to the target text. To achieve this, we will analyse the transfer through the lens of Descriptive Translation Studies (Toury, 2012). (2) To determine how sexual references are treated in the translated text, whether they are rendered using explicit sexual language or replaced with other taboo or offensive phrases. For this, we employ Ávila-Cabrera’s (2023b) taxonomy of translation techniques to examine the handling of these references and assess whether the taboo load is preserved in the subtitles. (3) To identify the most recurrent translation techniques used. Among the expected findings, we aim to test our initial hypothesis that considers that sexual phrases tend to be transferred as closely as possible in the subtitles in this TV series. In summary, our intention is to contribute to the literature of the treatment of sexual language in interlingual subtitling through this paper.